Social acceptance of small modular reactors - Shevchenko, Anton; Calic, Goran; Michael Lee-Chin & Family Institute for Strategic Business Studies (My University, 2023)
This study explores the complex process of how audiences perceive a novel technology by focusing on small modular reactors (SMRs), a promising nuclear energy technology. Contrary to the idea that acceptance is merely based on technical attributes, this research emphasizes the role of legitimacy perceptions in technology adoption. Leveraging the legitimacy framework, we analyzed a broad range of media articles on SMRs using a topic modeling algorithm. Our results reveal that legitimacy perceptions of SMRs are entangled with a vast array of concepts that are familiar to the audience, such as a given country’s unique needs and the pros and cons of existing alternative technologies. We found that audiences rely heavily on their knowledge of related concepts and imagination to form their perceptions of SMRs. Our study of technological legitimacy highlights the complexity of the social acceptance of a novel technology Valuation Insight: Adoption of a new technology depends on investor perceptions of its legitimacy. Aside from productivity-enhancing qualities, a technology’s perceived legitimacy is found to be an important additional attribute that significantly affects its implementability. Value created by novel technology depends on its perceived legitimacy, impacting both the valuation of developing and adopting firms.
33 p. ; Includes bibliographical references (pp. 29-31).